Kansas Provider Report of Adolescent Vaccinations in Their Practice - Padilla, Serina; Homan, Gretchen; Engel, Matt; Ahlers-Schmidt, Carolyn R.; Harris, Kari (Kansas Journal of Medicine, 2019)
Introduction. Kansas falls consistently below average for adolescent vaccination of meningococcal (MCV), human papillomavirus (HPV), and influenza. Methods. For this study, the members of Kansas Chapter of the American Academy of Pediatrics were emailed a confidential electronic survey soliciting their impressions of vaccination in their practice. Results. Of 137 providers emailed, 61 (45%) completed the survey. Thirteen providers were excluded as they did not see/vaccinate adolescents or did not complete the survey. Tetanus, diphtheria, pertussis (Tdap), and MCV vaccines were most commonly up to date with 31 (65%) and 20 (42%) respondents reporting greater than 90% immunization rates, respectively. HPV (n = 42, 89%) and influenza (n = 40, 83%) vaccines had refusal rates greater than 25% in most clinics. Most practices (n = 44, 92%) used internal electronic medical records to track vaccinations, although 29 practices (60%) utilized the state immunization information system. Providers requested vaccine-specific patient education tools, positive media coverage, staffing support, and best-practices workshops to support vaccination efforts. Conclusion. Kansas providers may not be optimizing available resources to enhance these rates, such as Web IZ tracking and immunization reminders. Patient education supplies, specific to HPV and Influenza vaccination, potentially could increase vaccination rates. KS J Med 2017;10(4):84-87.